Full-Text eBook Retrieval System in an Integrated Library Management System: Designing an Open- Source Technical Framework - Barman, Debabarata; Dutta, Anirban; Mukhopadhyay, Parthasarathi (Journal of Information and Knowledge, 2025)
The study introduces an eBook retrieval architecture designed to retrieve both metadata and full-text content. At its core, Koha serves as the Integrated Library System (ILS) at the back end, while VuFind provides the discovery layer at the front end. Metadata retrieval is based on the MARC 21 bibliographic format, with full-text links stored in tag 856. A key component is the full-text retrieval system, which utilises the open-source Apache Tika to analyse full-text objects. Extracted words and phrases are then sent to Apache-Solr for indexing. The architecture operates across three layers, with Koha managing the backend, Apache-Tika processing the full-text in the middle, and VuFind, powered by Apache-Solr, facilitating search and discovery at the front end. This structure enables efficient retrieval of both metadata and full-text, streamlining the process of locating eBook content through word and phrase search.